2019
DOI: 10.1177/0972150919837080
|View full text |Cite
|
Sign up to set email alerts
|

Spillover Effect of M&A Announcements on Acquiring Firms’ Rivals: Evidence from India

Abstract: Motivated by the paucity of empirical studies examining the impact of mergers and acquisition (M&A) announcements on the acquiring firms' rivals, we made an attempt to uncover the spillover effect of M&A announcements on the stock market reaction of acquiring firms' rivals. Using a sample of 97 M&A announcements during the period from April 2014 to March 2016 and 179 rivals of acquirers, we found that acquiring firms and acquiring firms' rivals react positively to the announcement of M&As. The results of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…The historical performance of stock markets has been documented in the previous literature regarding influenza and other major epidemics. Similarly, the scholars have examined the influences of significant events on the stock markets, i.e., Severe Acute Respiratory Syndrome (SARS), (Chen et al, 2018 ), natural disasters (Caporale et al, 2019 ), corporate events (Ranju and Mallikarjunappa, 2019 ), public news, and political events (Bash and Alsaifi, 2019 ). Some other studies have also demonstrated that SARS in 2003 weakened the Taiwanese economy (Chen et al, 2007 ) and regional stock markets (Chen et al, 2018 ).…”
Section: Effects Of Previous Pandemics On Stock Marketsmentioning
confidence: 99%
“…The historical performance of stock markets has been documented in the previous literature regarding influenza and other major epidemics. Similarly, the scholars have examined the influences of significant events on the stock markets, i.e., Severe Acute Respiratory Syndrome (SARS), (Chen et al, 2018 ), natural disasters (Caporale et al, 2019 ), corporate events (Ranju and Mallikarjunappa, 2019 ), public news, and political events (Bash and Alsaifi, 2019 ). Some other studies have also demonstrated that SARS in 2003 weakened the Taiwanese economy (Chen et al, 2007 ) and regional stock markets (Chen et al, 2018 ).…”
Section: Effects Of Previous Pandemics On Stock Marketsmentioning
confidence: 99%
“…Investors consider corporate actions taken by the company in making decisions. According to research by [102], most investors reacted positively to the announcements issued [103], [104], [105], [102]. Corporate action taken by the company is a signal for investors.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…The company's abnormal returns increase due to M&As [113]. Several previous studies have proven that investors respond positively to M&A [105], [114], [115], [116]. M&A provides benefits to shareholders, including the target company and the bidding company [107], [108].…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Mergers and acquisitions have been pursued by companies as an important growth strategy (Ranju & Mallikarjunappa, 2019). Domestic and cross-border M&A happen for a common reason, gaining synergy (Erel et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%